Does Financial Inclusion Affect Financial System Stability? Evidence from Indonesia - Meutia, Rachmi; Billa, Salsa (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
Financial system stability represents a fundamental component of the economy, as it facilitates the efficient functioning of financial transactions. It is argued that the financial inclusion tends to enhance the financial stability. This study aims to investigate the effect of financial inclusion variables through fintech integration specifically Peer-to-Peer (P2P) lending, E-Money, and Interest Rates on Financial System Stability (FSS) in Indonesia, with the Non-Performing Loan (NPL) ratio serving as a proxy. The analysis uses the Vector Error Correction Model (VECM) with monthly time series data from 2018-2023. The results of this study show that only the E-Money variable has a significant influence on Financial System Stability, both in the short term and the long term. In contrast, Peer-to-Peer lending and Interest Rates do not significantly affect Financial System Stability in either the short or long term. This study emphasizes the need for policymakers undertake comprehensive and well-considered policy measures in advance of implementing financial inclusion-oriented initiatives. It is recommended that financial institutions strengthen the supervision of peer-to-peer (P2P) lending activities to mitigate the risk of default. Furthermore, enhancing public awareness of the advantages of cashless transactions is essential to promote the adoption of non-cash payment instruments.